Pengendalian Intern Atas Pemberian Pinjaman dan Penerimaan Angsuran dalam Hubungannya dengan Ditaatinya Kebijakan Manajemen (Studi Kasus pada PT. Sumber Nasional Motor di Bandar Lampung) - Herry Goenawan Soedarsa; . Henny; Haninun HANINUN (Jurnal Akuntansi dan Keuangan, 2010)
The purpose of this study was to assess the procedures for granting loans and installment receipts from customers on PT National Sources Motors, to assess the extent of the workings of the employees in the procedures for granting loans and installment receipts from customers on PT. National sources motors, to study the division of labor system imposed by PT. National Sources Motors and its application in lending procedures and installment receipts (whether or not adhered to company policy), and to compare between the existing theory and practice in lapangan.alat analysis is qualitative analysis tool. Qualitative analysis is a tool used analysis tool by comparing the theory with the practice in the company without using numbers or calculations.From the results of research and analysis by the author, it can be concluded that the PT SNM has not been fully successful in implementing good internal control procedures for granting loans and installment receipts from customers, where there are 3 elements of internal control that has not been applied to the maximum, ie labor competent and trustworthy, with the lines of authority and responsibility are clearly defined; adequate segregation of duties (segregation of duties), and healthy practices that should be run in the tasks and functions of each part of the organization.